2020
DOI: 10.3390/vaccines8020313
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Response against Hepatitis C Virus: Targets for Vaccine Adjuvants

Abstract: Despite successful treatments, hepatitis C virus (HCV) infections continue to be a significant world health problem. High treatment costs, the high number of undiagnosed individuals, and the difficulty to access to treatment, particularly in marginalized susceptible populations, make it improbable to achieve the global control of the virus in the absence of an effective preventive vaccine. Current vaccine development is mostly focused on weakly immunogenic subunits, such as surface glycoproteins or non-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 184 publications
(211 reference statements)
0
8
0
Order By: Relevance
“…The protection provided was no greater than that provided by the placebo[ 112 ]. Recent investigation on HCV vaccine adjuvants demonstrated that the induction of a strong T and B cell immunity is enhanced by choosing the right adjuvant[ 113 ]. The subject of vaccines producing neutralizing antibodies has also been briefly reviewed in two recent editorials[ 114 , 115 ].…”
Section: Can We Eradicate Hcv By 2030 With Daas Treatment?mentioning
confidence: 99%
“…The protection provided was no greater than that provided by the placebo[ 112 ]. Recent investigation on HCV vaccine adjuvants demonstrated that the induction of a strong T and B cell immunity is enhanced by choosing the right adjuvant[ 113 ]. The subject of vaccines producing neutralizing antibodies has also been briefly reviewed in two recent editorials[ 114 , 115 ].…”
Section: Can We Eradicate Hcv By 2030 With Daas Treatment?mentioning
confidence: 99%
“…Unfortunately, a phase I/II study in PWID population showed that this vaccination strategy was not effective for preventing chronic infections since T cell exhaustion was not reversed (ClinicalTrials.gov Identifier: NCT01436357[ 193 ])[ 194 , 230 ]. These results highlight the need for a vaccine strategy that stimulates both humoral and T cell immunity[ 23 , 231 ]. However, attempts to enhance CMI without the need of boosting the generation of Abs, have been addressed in pre-clinical studies on non-human primates by fusing the HCV non-structural antigen to MHC class II-associated invariant chain[ 232 ].…”
Section: Approaches To Design Vaccine Candidates For Hcvmentioning
confidence: 99%
“…When NS3 DNA vaccine was co-administered with interleukin-12 as adjuvant, strong immunogenicity was also displayed in murine models[ 258 ]. Several other adjuvants have also been employed in NS3-based DNA vaccination in order to enhance their potency (for a detailed review see Sepulveda-Crespo et al [ 231 ] 2020). In addition, constructs encoding a codon-optimized NS5A injected IM into mice, in combination with in vivo electroporation, were also able to prime specific T cell responses[ 259 ].…”
Section: Approaches To Design Vaccine Candidates For Hcvmentioning
confidence: 99%
“…Alternatively, advances in vaccine adjuvant, immunopotentiator, and vaccine particle development offer the potential to trigger multiple immune pathways with a single vaccine platform, such as recombinant protein antigens that with certain adjuvants not only trigger robust B cell and CD4 + T cell responses but also induce cross-presentation to CD8 + T cells. Numerous such platforms are being actively evaluated in pre-clinical and limited clinical studies of new HCV vaccines, and recent reviews have examined this in more comprehensive detail [ 113 , 114 ].…”
Section: Harnessing Neutralizing Antibody Responses In New Vaccinesmentioning
confidence: 99%